ON THE SPECIFIC FEATURES OF THE POETIC IDIOSTYLE OF B. L. PASTERNAK - N. Tsareva (Гуманитарные и юридические исследования)
The article describes the basic features of the idiostyle of the great Russian poet of the twentieth century B. L. Pasternak. The analysis is carried out taking into account the anthropogenic approach to the text based on the study of authoritative research in the field of discourse, style studies, text linguistics, cultural linguistics, cognitive linguistics, philological analysis, verse studies, philosophy and other areas of modern scientific knowledge. The “structure” of images, thoughts, feelings, sounds “is that” rational kernel “that motivates the question of the specificity of the author’s idiostyle as a subjective, individually felt construction of a text space. Considering Pasternak’s poetic text as an immanently organized artistic structure, the author of the article believes, not without reason, that the line of poetry itself creates conditions conducive to the formation of syntactic segments, in which “fluctuating signs of meanings” and “darkened meanings” of naming world phenomena appear. In this case, the artist of the poetic word receives not only complete freedom of choice and the main attributes of the denotation, its details and the circumstances accompanying the disclosure of the signs of the signified, but also the opportunity to create new nominal structures in the text space containing elements of meta-commentary, including subjectiveevaluative moments, fixing the author’s presence in the text. The article notes that the use of syntactic nomination by BL Pasternak as the structure of the “frozen moment” of poetic life is associated with the identification of the deep semantic coherence of its elements. The reasoning contained in the article leads the reader to the conclusion that as the lyrical hero Pasternak matures, there is a transformation in the ratio of text and metatext caused by changes in the manifestation of the author’s individual perception of the world.